Scale Structure and Reflectance Activity of Metapocyrtus apoensis with Notes on Its Distribution in Mindanao, the Philippines - Romeo R. Patano Jr.; Joriegae M. Abales; Erika J. Bajuyo; Ara Belle R. Magtulis; Rainear A. Mendez; Rhesa T. Hinampas (Tropical Life Sciences Research, 2021)
Scale structure and reflectance activity of a Mindanao endemic weevil from the genus Metapocyrtus has been studied for the first time. Specimens of Metapocyrtus apoensis Schultze, 1925 were collected through opportunistic sampling in Mount Calayo, Musuan, Mindanao, Philippines last February 2020. A total of three individuals of the species were collected all in lower dipterocarp forest with elevation of 500 masl–600 masl. Three specimens were then examined under Scanning Electron Microscopy with Energy Dispersive X-Ray (SEM_EDX) to analyse its scale structures and reflectance activity. The study provides new locality record of the Mindanao endemic species first in Bukidnon region and an updated distribution in Mindanao based on recent published articles and museum collections. The species inhabits wide ranges of habitat types that greatly differ in elevation and vegetation. Examination of scale’s structure through SEM revealed that M. apoensis scales are 50 ?m–70 ?m in diameter which are almost circular in shape, slightly convex with rough like surface which is termed as non-ordered nipple-like structure. The scales’ shape and surface structure clearly differ from other genera of curculionids based on published articles. Analysis of the particles on the weevil’s elytra done by EDX reveals several elements that contribute to its iridescence. Major elements such as Carbon (42.3%), Oxygen (27.7%) and Nitrogen (15.1%) come in relatively high atomic concentrations. Microspectrometer revealed a peak reflectance wavelength of about 569.7 nm. This explains the yellow-green iridescence observed on the dorsal side of the weevil. The concentration of the scale in pits serves for protection, intraspecific recognition and camouflage. Despite of widespread distribution and high abundance of this species in Mindanao, anthropogenic disturbances such as agricultural activities are on-going which extend towards their microhabitat. Monitoring to its population is recommended as the species is restricted only in Mindanao.